Antifungal activity of selected volatile essential oils against Penicillium sp. - Felšöciová, Soňa (Open Life Sci, 2020)
Phytopathogenic fungi have been responsible for considerable economic losses in vineyards, and therefore, more attention should be paid to the development and implementation of preventative treatment that is environmentally friendly. The aim of this study was to evaluate the antifungal activity of ten essential oils (EOs) (viz. Lavandula angustifolia Mill., Carum carvi L., Pinus mugo var. pumilio, Mentha piperita L., Foeniculum vulgare L., Pinus sylvestris L., Satureja hortensis L., Origanum vulgare L., Pimpinella anisum L. and Rosmarinus officinalis L.). For the antifungal activity evaluation against Penicillium brevicompactum, P. citrinum, P. crustosum, P. expansum, P. funiculosum, P. glabrum, P. chrysogenum, P. oxalicum, P. polonicum and Talaromyces purpurogenus a disc diffusion method was used. The ten EOs exhibited different antifungal properties. Three tested EOs (Carum carvi L., Satureja hortensis L. and Pimpinella anisum L.) at concentrations of 0.75, 0.50, 0.25 and 0.125 µL/mL showed antifungal activity, inhibiting the mycelial growth. The Origanum vulgare L. EOs exhibited a lower level of inhibition. Overall, Lavandula angustifolia Mill., Pinus mugo var. pumilio, Mentha piperita L., Foeniculum vulgare L., Pinus sylvestris L., Satureja hortensis L., Pimpinella anisum L. and Rosmarinus officinalis L. were effective as fungicidal agents but their efficiency varied between the strains of fungi. Carum carvi L. showed strong antifungal activity against all tested strains at both full strength and reduced concentrations. These EOs could be considered as potential sources of antifungal compounds for treating plant fungal diseases.